Hidrogenação de CO2 a produtos com dois ou mais átomos de carbono: catalisadores promissores, desafios e perspectivas - Bueno, Leonardo Martins Silveira (Universidade Federal de São Carlos, 2020)
The catalytic hydrogenation of CO2 has been intensively studied, since it is one of the most promising ways to use carbon from the atmosphere. Compared to CO2 hydrogenation to methanol, the synthesis of ethanol or other higher alcohols is much more challenging, since it requires the formation of a C-C bond and the retention of a C-O bond, however ethanol has a greater energy density than methanol. This work presents a bibliographic review of the recently published works about the hydrogenation of CO2 to ethanol and higher alcohols, the advances and barriers found and perspectives to be explored in the future. Several materials have been investigated for the catalysis of CO2 to ethanol, we can highlight Cu-based catalysts, noble metal catalysts and Co based catalysts. The Zr12-bpdc-CuCs catalyst presented the best result, with high selectivity to ethanol and CO2 conversion, more than 99% and 96%, respectively, at 100 °C. The Cu @ Na-Beta catalyst has also shown good selectivity to ethanol, 79%, however, the ethanol conversion was 18% and the operation temperature was higher, 300 °C. The CuII(HxPO4)y@Ru-UiO and Pd-Fe3O4 catalysts, although exhibiting a selectivity to ethanol greater than 95%, presented a very low CO2 conversion, less than 1%. The Au-TiO2 and PdCu-TiO2 catalysts, which operated in batches at 200 °C, also showed high selectivity to ethanol, greater than 90%, but no data on CO2 conversion were reported. Although most studies are carried out in packed bed reactors (PBR), the best results were obtained in batch. The main challenges to be overcome are low selectivity to higher alcohols, low catalyst stability and/or low CO2 conversion. In addition, for the process to be environmentally sustainable, it is necessary that renewable sources of hydrogen are used.
Hydrogenation of CO2 to products with two or more carbon atoms: promising catalysts, challenges and perspectives
Keywords: Hidrogenação de CO2; Catalisadores; Etanol; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA